Reliability and validity of the Danish version of the Self-Assessment of Modes Questionnaire. (19th May 2023) - Pilegaard, Marc Sampedro; Nielsen, Kristina Tomra; Enemark Larsen, Anette; Wæhrens, Eva Ejlersen
Abstract: Background: The Self-Assessment of Modes Questionnaire (SAMQ) is developed to help therapists identify their preferred use of modes when interacting with clients in clinical practice. A Danish translation of the SAMQ has been developed (D-SAMQ). To provide a robust instrument for occupational therapy practice and research, evaluation of the psychometric properties of the D-SAMQ is needed. Objectives: The study aims to evaluate test-retest reliability, measurement error and content validity in terms of cultural relevance of the D-SAMQ. Material and methods: Danish occupational therapists were recruited to represent diverse clinical settings and to work with various age groups. The D-SAMQ consists of 20 clinical cases. A repeated measures design was employed with evaluation of content validity at the second timepoint. The Content Validity Index and Kappa statistics were employed. Results: In most cases ( n = 12, 60%) agreement (test–retest reliability and measurement error) was moderate or strong. Also, there was a moderate ( n = 6 cases, 30%), strong ( n = 4 cases, 20%) or almost perfect agreement ( n = 10 cases, 50%) on the cultural relevance of the cases. Conclusions: Acceptable test–retest reliability, measurement error and content validity were found. The SAMQ may support occupational therapists to adapt their therapeutic style to meet the needs of the clients.